STUDI PERILAKU MASYARAKAT PERAMBAH HUTAN DALAM REHABILITASI KAWASAN KONSERVASI DI DESA BUMI AGUNG KECAMATAN WARKUK RANAU SELATAN KABUPATEN OGAN KOMERING ULU SELATAN - Hidayat, Yayat; Sriati, Sriati; Sufri, Marwan Sufri (Universitas Muhammadiyah Palembang, 2014)
Forest encroachers is a classic problem that can not be resolved completely. Formal juridical approach often involves the re-emergence of complex issues, among others, and the future movement of anarchy that ultimately the completion of the main problems is not a new problem arises. Forest management paradigms must be run from stand -based forest management based conflict resolution. Community forest encroachers Forest Preserve Mountain Kingdom not existed since the 1970s, sporadic and hereditary manage forests into coffee plantations. In the era of the 1990's has been done but the preconditions and decrease gradually forced browser society do the activity again. Along with forest encroachment, forest management Mountains Wildlife Kingdom at the unit level management has approached the forest encroachers and encourage people to manage forests to balance conservation approach that is the behavior of the people who helped to prevent, maintain, restore forest encroachers with rehabilitation self.